2024
DOI: 10.1037/sgd0000632
|View full text |Cite
|
Sign up to set email alerts
|

Gender variance and psychological well-being in Chinese community children.

Abstract: Childhood gender variance (GV) and its association with psychological well-being have garnered increasing interest recently but little is known about children from the community and non-Western samples. Therefore, we examined GV and its associations with psychological well-being in a Chinese community sample where study of childhood GV is extremely rare. Parents of 461 Chinese children aged 4–12 years (243 birth-assigned males) provided information on GV using the Gender Identity Questionnaire for Children (GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This study is part of a larger project examining GD in Chinese community children. Our previous study (Wong et al, 2023) reported results on the relationship between GD and psychological well-being (happiness, self-worth, behavior challenges, and peer relations), whereas the current study focused on the GD-autism trait co-occurrence. Ethics approval was obtained from the departmental research ethics committee.…”
Section: Methods Participantsmentioning
confidence: 88%
See 4 more Smart Citations
“…This study is part of a larger project examining GD in Chinese community children. Our previous study (Wong et al, 2023) reported results on the relationship between GD and psychological well-being (happiness, self-worth, behavior challenges, and peer relations), whereas the current study focused on the GD-autism trait co-occurrence. Ethics approval was obtained from the departmental research ethics committee.…”
Section: Methods Participantsmentioning
confidence: 88%
“…These hypotheses may hold particular significance within the Chinese context. While research on GD among Chinese children is still emerging (Wong et al, 2023;Yu & Winter, 2011), existing studies indicate that both Western and Chinese children experiencing GD encounter psychosocial challenges, with potentially heightened implications for Chinese children. For example, children from Canada showed less bias against gender-diverse children than did Chinese children and may be more accepting of gender-diverse children (Kwan et al, 2020;Nabbijohn et al, 2020); on the other hand, traditional Chinese cultural values such as Confucianism T A B L E 1 Hierarchical regression models with AQ (full scale) and its associations with the GIQC as the dependent variable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations